Blended Online Intervention to Reduce Digital Transformation Stress by Enhancing Employees’ Resources in COVID-19 - Makowska-Tłomak, Ewa; Bedyńska, Sylwia; Skorupska, Kinga; Paluch, Julia (Frontiers in Psychology, 2022)
Generally, the solutions based on information and communication technologies (ICT) provide positive outcomes for both companies and employees. However, the process of digital transformation (DT) can be the cause of digital transformation stress (DTS), when the work demands caused by fast implementation of ICT are elevated and employees’ resources are limited. Based on the Job Demand-Resources (JD-R) Model we claim that DT, rapidly accelerating in the COVID-19 pandemic, can increase the level of DTS and general stress at work. To reduce these negative effects of DTS, we propose the online intervention aimed to strengthen employees’ resources, such as self-efficacy. In this article we evaluate the effectiveness of the blended intervention, based on cognitive behavioral therapy (CBT) and social cognitive therapy, composed of a prototyped online training (e-stressless) and series of interactive online workshops. In a longitudinal study, we examined the change in DTS, perceived stress at work, attitudes towards DT, self-efficacy and burnout in two time points, before and after the intervention. We compared five groups of participants (558 in total), three groups not qualified (n=417), and two groups qualified to intervention (n=141). Our results revealed that the designed blended intervention decreased DTS and one of the dimensions of burnout, namely disengagement. More specifically, the results showed that in the group of active participants of the blended intervention DTS significantly decreased (MT1 = 3.23, MT2 = 3.00, t (432) = 1.96, p = 0.051), and in the group of ineligible participants DTS significantly increased (MT1 = 1.76, MT2 = 2.02, t (432) = 4.17, p < 0.001). This research paves way for the creation of blended online intervention which could help in addressing employee digital transformation stress before it starts having adverse effects on employee performance and well-being.